Crypto Asset Audits in the Era of Decentralized Finance (DeFi): A Global Systematic Review - Pardomuan Pardosi; Tussi Sulistyowati; Khairil Anwar; Maria Yovita R Pandin; Amiartuti Kusmaningtyas (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. This research explores global studies on crypto asset audits in Decentralized Finance (DeFi) from 2021 to 2025 through a systematic literature review (SLR) approach, highlighting technological advancements like machine learning and hybrid analytics that enhance audit accuracy, fraud detection, and scalability. Purpose. Auditing practices have expanded to include smart contracts, compliance, security, and environmental audits. However, challenges persist, such as the lack of global regulatory standards, decentralized control, security risks, and instability within DeFi protocols. Method. Despite advancements, effective audits in DeFi require aligning technological innovation with adaptable regulatory frameworks to ensure sustainability and trust. Results. Managerially, DeFi platforms should integrate emerging technologies into auditing practices and collaborate with regulators to address compliance gaps, particularly in anti-money laundering (AML) and transparency.   Conclusion. Future research should focus on developing global DeFi regulations, exploring decentralized auditing methods, and investigating the impact of new financial systems like the metaverse on auditing practices.